Marx y los fundamentos crítico-filosóficos de la esfera pública - Jurado-Castaño, Pedro Alejandro (2022)
This paper presents the presuppositions that enable a critical reflection on the public sphere from a Marxist perspective. It begins by considering the contextof recent discussions concerning Marx’s political ideas, and the relevance of the concept of public sphere in order to show the importance of some of Marx’s critical concepts for political philosophy. The text is the result of a research project aimed at constructing a conceptual framework to develop a critical analysis of the public sphere today. This research has already established that some key issues, linked to the concepts of language and experience, were present in Marx’s work. In this sense, the paper presents a novel reflection to the extent that it deals with the actuality of Marx’s thought through the analysis of a contemporary political problem that allows to highlight the critical and radical implications that Marx’s philosophical-critical foundations have for contemporary discourse and politicalinstitutions such as the public sphere.